Tackling Ireland’s Psychologist Shortage: The Need for Educational Innovation - Aleksandra Szproch; Rebecca Kummer; Ke Ren; Eileen Winter; Deirdre MacIntyre; Moya O'Brien (Irish Journal of Technology Enhanced Learning)
In Ireland, a critical shortage of psychologists is impacting health, education, and social care services. This deficit, exacerbated by the COVID-19 pandemic, has led to prolonged waiting times for psychological services, adversely affecting the timely support and wellbeing of individuals in need. Despite government initiatives to reduce waiting lists, such as the recent funding for additional private Assessments of Need (AON), long-term solutions, including increased investment in innovative training opportunities, remain undeveloped. This paper advocates for expanding access to psychology education and training through blended and online learning models. Such an approach would enhance accessibility, inclusivity, and flexibility in training, addressing both immediate and systemic challenges. By drawing on the UK's 'Psychological Professions Workforce Plan for England' (National Health Service, 2021) and integrating blended and online learning into psychology education, Ireland can build a sustainable and diverse psychological workforce.